Reviews and Responses for Data-Driven Prediction of Aircraft Holding Times Using OpenSky Data - Vella, Michele; Gauci, Jason; Dingli, Alexiei; Li, Max; Dalmau, Ramon; Krauth, Timothé (Journal of Open Aviation Science, 2025)
See detailed reviews and responses in the PDF file. DOI for the original paper: https://doi.org/10.59490/joas.2024.7890